Particular, Universal, and Salvation in Continuity in the Gospel of Matthew - Saragih, Erman Sepniagus (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: This text reviews the multidimensional and problematic construction of the doctrine of salvation based on reading the study of the Gospel of Matthew. The existence of the multiplicity of creation causes the concept of salvation and how that salvation is achieved to vary greatly (diversity). The research method used is descriptive qualitative with a critical and constructive literature study approach. The Gospel of Matthew emphasizes the meaning of salvation that is particular, universal, and sustainable. Particular salvation is understood from the way Matthew conveys the structure of his gospel from the genealogy of Jesus with nuances of genealogy and Jewish tradition. Universality means that from particularity into ethnically diverse communities in Christ's work of salvation is necessary. For Matthew, Jesus' rescue was affirming and upholding the continuity of God's saving relationship with His people, which began with Abraham, the consummation of the Law, and the continuing validity of all that was done, given, initiated, and instituted by God in history to save his people, as well as God's constant invitations for his people to enter into and remain in a saving relationship.Â Keywords: Particular, Universal, Continuity Salvation, Gospel of Matthew